Victimes et bourreaux dans le théâtre de Griselda Gambaro De "El desatino" (1965) à Antígona furiosa (1986) - Sureda-Cagliani, Sylvie (Études, 2011)
This studying attemps to go more deeply into the cultural, historical and social context which is the backdrop to Griselda Gambaro's theatrical world from the 1960s onwards. In Argentina during the years of repression, first under the dictatorship of Juan Carlos Onganía (1966) then that of Rafael Videla (1976), the theatre was a form of escapism, yet at the same time a means of expression staging human mores and behaviour. The plays analysed here denounce the perversion of dictatorship as well as the suffering inflicted on victims by their torturers. In this specific political and social context, the theme of "victim and torturer" is a constant in these theatrical works, which underline the dangers of coercion and arbitrary decisions exercised by tyrannical power.